Investigating the solid waste recycling management - Hazheer, Abdul wali; Ehsan, Hamayon; Anwari, Gulaqa (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Garbage is waste solid materials that are left over from the use of people and production and service institutions and are unusable. These seemingly inefficient sources are the most important urban pollutant in different amounts and in liquid and solid form and cause harm. and the citizens' interest, but in the case of optimal management and use of these valuable resources as raw materials in addition to protecting the environment, reducing the level of pollution, reducing the amount of diseases and deaths, it can be considered the best driver of production activities, recycling management Household solid waste in Kabul city is handled according to municipal standards and regulations (collection, transfer, burial and reuse), which is the main goal of this research to investigate the effects of household solid waste management and recycling in Kabul city. Since the nature of this research is descriptive-applicative, in order to collect information from two sources, the library and a questionnaire with a 7-point Likert scale from 384 citizens of the 15th district of Kabul city were randomly sampled and analyzed using spss software. First, the confidence level of the questionnaire of both variables was determined by Cronbach's alpha method with the output coefficient (waste management 0.86 and recycling rate 0.82) and then its correlation intensity was determined by the Pearson method and also to predict the dependent variable from the linear regression function of the information received and investigated. And the dispute has been placed. Pearson's correlation analysis with 95% confidence level of the number placement (p=0.004, N=384, R=0.86) with a coefficient of determination of 0.73 and a statistical value (t) of 4.76, which is greater than the critical value of table t 2.3, shows the relationship There is a strong positive among the variables and it states that the increase in the amount of recycling and the decrease in the consumption of family solid waste depends on the improvement of waste management, in the same way, the beta coefficient of 0.59 and t=7.31>1.96 and sig<0.05 of linear regression were obtained. It shows that improving family solid waste management will reduce the amount of waste consumption and recycling by 59%, also the extracted information shows that about 97% of household waste is bought and collected by informal garbage collectors.